Ruptured giant thoracic hydatid cyst presenting with respiratory symptoms - Reza Ershadi; Hesam Amini; Ghazal Roostaei; Hossein Kazemizadeh; Leila Mollamohammadi; Niloofar Khoshnam Rad (Respirology Case Reports, 2024)
Key message Pulmonary hydatid disease remains a global public health issue. Symptoms often result from cyst rupture, causing fever, cough, and hemoptysis. Radiographs may show homogeneous masses, air‐fluid levels, or the pathognomonic “water lily” sign. Surgical removal is the primary treatment, with early diagnosis crucial to prevent acute hypersensitivity reactions and death.